UNDERSTANDING AND EVALUATING THE ENFORCEMENT OF CORPORATE LAW IN NIGERIA: THE CASE FOR ENHANCED PUBLIC CIVIL ENFORCEMENT - AWOLALU, OLUDARA,AJIBIKE (2017)
In recent years, countries around the world have witnessed a number of corporate scandals, varying in their enormity. Nigeria has been no exception, having suffered its fair share of these corporate scandals. In many countries, the discovery of some new corporate scandal is unsurprisingly accompanied by calls, from various quarters, for increased directorial accountability. Such calls are then, in their turn, followed by the introduction of new corporate and securities regulations, as well as reforms to existing corporate governance codes. In this quest for increased directorial accountability however, almost all the attention tends to be placed on the substantive content of the laws and codes governing directors. Much less attention, by contrast, has been devoted to the effectiveness of the enforcement regimes applying to these laws and codes. Yet, in the absence of effective enforcement, substantive rules have little impact. Consequently, while it is important to have appropriately developed company law regimes, which impose duties and responsibilities on directors, such laws are likely to fall well short of the mark unless they are also well enforced. It therefore becomes necessary to examine critically enforcement within the context of corporate law. In light of the crucial importance of enforcement in securing directors’ compliance and accountability, this thesis focuses upon the enforcement of corporate law in Nigeria. It analyses three major enforcement regimes in Nigeria: the criminal enforcement regime, the private civil enforcement regime and the public civil enforcement regime. Drawing on criteria for determining effective enforcement developed in the course of this thesis, it argues that the public civil enforcement regime offers the best potential for achieving significant real improvement in the enforcement of corporate law in Nigeria. To further reinforce the argument made for an enhanced public civil enforcement regime, this thesis uses three enforcement case studies derived from the UK and from Australia. The enforcement experience in these countries, whose corporate law regimes bear close similarities with that of Nigeria, have revealed that the public civil enforcement regime, by a clear gap, offers a potentially effective enforcement regime in corporate law. In short, then, this thesis argues that attaining effective enforcement of corporate law is within Nigeria’s reach but this can however be achieved only if it reforms, and develops, public civil enforcement in order to realise the potential benefits of this enforcement regime